2021
DOI: 10.1111/cts.13149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of atezolizumab immunogenicity: Efficacy and safety (Part 2)

Abstract: Antibody therapeutics can be associated with unwanted immune responses resulting in the development of anti-drug antibodies (ADA). Optimal methods to evaluate the potential effects of ADA on clinical outcomes in oncology are not well established. In this study, we assessed efficacy and safety, based on ADA status, in patients from over 10 clinical trials that evaluated the immune checkpoint inhibitor atezolizumab as a single agent or as combination therapy for several types of advanced cancers. ADA can only be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…18 The clinical impact of atezolizumab immunogenicity was evaluated previously across the monotherapy and combination therapy clinical studies. 19,20 The results showed that ADA impacts atezolizumab CL minimally (16% increase in time-stationary popPK model and 9% increase in time-varying popPK model), 9,12 and that its impact on atezolizumab exposure was not clinically meaningful. 19 There was no statistically significant impact on efficacy or safety across the exposure ranges tested.…”
Section: Discussionmentioning
confidence: 98%
“…18 The clinical impact of atezolizumab immunogenicity was evaluated previously across the monotherapy and combination therapy clinical studies. 19,20 The results showed that ADA impacts atezolizumab CL minimally (16% increase in time-stationary popPK model and 9% increase in time-varying popPK model), 9,12 and that its impact on atezolizumab exposure was not clinically meaningful. 19 There was no statistically significant impact on efficacy or safety across the exposure ranges tested.…”
Section: Discussionmentioning
confidence: 98%
“…All EC and IRB forms are provided as Appendix S3. Some of the trials investigated in recent analyses of atezolizumab immunogenicity were not considered in the present study due to a lack of consent language for exploratory genetic analyses in the trial protocols 5,6 …”
Section: Methodsmentioning
confidence: 99%
“…Some of the trials investigated in recent analyses of atezolizumab immunogenicity were not considered in the present study due to a lack of consent language for exploratory genetic analyses in the trial protocols. 5,6 Detection and analysis of ADA and NAb status ADA and NAb incidences were systematically and consistently assessed in atezolizumab-treated patients in all studies. Analytical methods were developed and run in accordance with industry best practices and health authority guidelines, and are described in more detail in Appendix S1.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
See 2 more Smart Citations